Parametric study on tensile and flexural properties of ULTEM 1010 specimens fabricated via FDM. Issue 2 (1st February 2021) - Pandelidi, Chrysoula; Maconachie, Tobias; Bateman, Stuart; Kelbassa, Ingomar; Piegert, Sebastian; Leary, Martin; Brandt, Milan
Abstract : Purpose: Fused deposition modelling (FDM) is increasingly being explored as a commercial fabrication method due to its ability to produce net or near-net shape parts directly from a computer-aided design model. Other benefits of technology compared to conventional manufacturing include lower cost for short runs, reduced product lead times and rapid product design. High-performance polymers such as polyetherimide, have the potential for FDM fabrication and their high-temperature capabilities provide the potential of expanding the applications of FDM parts in automotive and aerospace industries. However, their relatively high glass transition temperature (215 °C) causes challenges during manufacturing due to the requirement of high-temperature build chambers and controlled cooling rates. The purpose of this study is to investigate the mechanical properties of ULTEM 1010, an unfilled polyetherimide grade. Design/methodology/approach: In this research, mechanical properties were evaluated through tensile and flexural tests. Analysis of variance was used to determine the significance of process parameters to the mechanical properties of the specimens, their main effects and interactions. The fractured surfaces were analysed by scanning electron microscopy and optical microscopy and porosity was assessed by X-ray microcomputed tomography. Findings: A range of mean tensile and flexural strengths, 60–94 MPa and 62–151 MPa, respectively, were obtained highlighting the dependence of performance on process parameters and their interactions. The specimens were found to fracture in a brittle manner. The porosity of tensile samples was measured between 0.18% and 1.09% and that of flexural samples between 0.14% and 1.24% depending on the process parameters. The percentage porosity was found to not directly correlate with mechanical performance, rather the location of those pores in the sample. Originality/value: This analysis quantifies the significance of the effect of each of the examined process parameters has on the mechanical performance of FDM-fabricated specimens. Further, it provides a better understanding of the effect process parameters and their interactions have on the mechanical properties and porosity of FDM-fabricated polyetherimide specimens. Additionally, the fracture surface of the tested specimens is qualitatively assessed.